Relações pedagógicas e práticas socioambientais: Uma prática de sistematização de experiência - Galarraga, Ana María Formoso (Universidade do Vale do Rio dos Sinos, 2013)
The thesis has its genesis in the weft of the complexity of human relations. It tries to analyze the relationship of collective emancipation and at the same time the ambiguities in an association of women (Associação Mundo + Limpo) and its relations with other institutions. The methodology chosen, the Systematization of Experience has prevailed throughout the work. All the different bonds are pointed out silences as resistance to certain practices and strategies of close association and work that were reflected vitally and with the collaboration of different social indicators and environment. The process of the Systematization of Experience was developed during two years (2010-2012) making visible weaknesses and strongholds that happen and are cultivated in everyday life of local and global relations. The theoretical perspective is based on notions of Michel de Certeau and Paulo Freire, which contemplates the anthropological complexity of "poacher and hope", fleeing from mysticism or passivity of hopelessness. One of the search results was the appropriation of the methodology chosen, which is formative and allows gathering and rethinking daily practices. It is a methodological path that moves from within diagrams, concepts, attitudes of own spaces, reading favorable things and criticisms on the way done. The written record allows that other practices can be systematized closer to the complexity of reality. The fact that research is done in a participatory way, makes people, not accustomed to this practice, can enrich and realize rich reflections about their daily work and relations. The survey wishes to collaborate with researchers, and commissions that are willing to make trails of resistance to capitalist individualism that shatters the knowledge and leaves invisible the collective practices that need to be thought out.
Keywords: Mulheres; Associações populares; Sistematização de experiências; Ecopedagogia; Emancipação coletiva; Women; Popular associations; Experiences systematization; Eco-pedagogy; Collective emancipation; ACCNPQ::Ciências Humanas::Educação